Research Mapping on Batik in Scopus-Indexed Publications - Aulianto, Dwi Ridho; Wardian, Wendia Kusuma; Auliani, Wulan Suci Intan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
This research aims to survey the field of batik-related studies within the Scopus database. The chosen methodology involves bibliometric analysis, utilizing the keyword "Batik" to gather data from Scopus. The collected data is then processed and examined through the Publish or Perish and VOSviewer applications to present visualization results. The findings of the study reveal a surge in scientific publications on batik in 2020, totaling 215 documents. Notably, Widiaty emerges as the most prolific author, contributing 16 papers. Indonesia stands out as the leading country in producing publications on batik, with Diponegoro University being the most affiliated institution. Scientific articles represent the predominant document type, accounting for 731 reports. Among these, documents categorized as "All Open Access" reached 66 in number. The total number of citations from 1901 to 2023 amounts to 5,414, with an average of 44.38 citations per year and 3.87 citations per article or document. The highest number of article citations, 405, was recorded for Syakur et al. in 2018. Furthermore, various citation metrics were assessed, including an h-index of 27, g-index of 45, hI norm of 17, HLA of 0.14, and hA-index of 9.